Analisis Sebaran dan Kerapatan Hutan Mangrove Menggunakan Landsat 8 di Kabupaten Tanah Bumbu Kalimantan Selatan - Mikhail Rohim; Ichsan Ridwan; Fahruddin Fahruddin (Universitas Lambung Mangkurat, 2021)
Mangroves are plants that live on beaches and river mouths, where these areas experience ups and downs of sea water. Around 3 million hectares of mangrove forest grow along 95,000 kilometers of Indonesia's coast, which is 23% of the world's total mangrove ecosystem. Indonesia's mangrove ecosystems are located in Papua, Kalimantan and Sumatra. This study aims to measure the distribution and density of mangrove forests in Tanah Bumbu Regency, South Kalimantan using Landsat 8 imagery with the support vector machine (SVM) classification method. Meanwhile, the density value was determined using the Normalized Difference Vegetation Index (NDVI) method. The results show that the mangrove distribution area is 2448.84 ha, of which the widest mangrove distribution is in the Simpang Empat area with an area of 1702.62 ha. Based on these results, it shows that the mangrove forest area in Tanah Bumbu Regency still has a fairly dense mangrove area.